Thank you for the opportunity to help you with your question!

(x² - 7x + 12)/(x² + 4x + 3) =1 - (x - 4)/(x² + 4x + 3)

so :

(x² - 7x + 12)/(x² + 4x + 3) =(x² + 4x + 3)/(x² + 4x + 3) - (x - 4)/(x² + 4x + 3)

(x² - 7x + 12)/(x² + 4x + 3) =((x² + 4x + 3) - (x - 4))/(x² + 4x + 3)

so:

(x² - 7x + 12)/(x² + 4x + 3) =((x² + 3x - 1))/(x² + 4x + 3)

(x² - 7x + 12) =(x² + 3x - 1)

- 7x + 12 - 3x + 1 = 0

- 10x + 13 = 0

so ;

x = 13/10

if you don't understand something please just ask

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up